2014
DOI: 10.1097/hcr.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Greater Improvement in Cardiorespiratory Fitness Using Higher-Intensity Interval Training in the Standard Cardiac Rehabilitation Setting

Abstract: Among patients with stable coronary heart disease on evidence-based therapy, HIIT was successfully integrated into a standard CR setting and, when compared to MCT, resulted in greater improvement in peak exercise capacity and submaximal endurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 18 publications
8
104
1
7
Order By: Relevance
“…Similar benefits were found for HIIT versus CAET for VĖ=VĊO 2 slope, oxygen uptake efficiency slope [43], partial pressure of end-tidal CO 2 [48], coronary atheroma and plaque characteristics [44] and quality of life [49]. Furthermore, some studies evaluated HIIT versus CAET for effects on blood pressure [43,47,[50][51][52], HR recovery and HR variability [51] as well as systolic function and systolic volumes [29,49] and found no effects of training on these variables. Finally, CAET seemed to confer better improvement in endothelial function as compared with HIIT [52].…”
Section: Hiit Versus Caet Programssupporting
confidence: 63%
See 2 more Smart Citations
“…Similar benefits were found for HIIT versus CAET for VĖ=VĊO 2 slope, oxygen uptake efficiency slope [43], partial pressure of end-tidal CO 2 [48], coronary atheroma and plaque characteristics [44] and quality of life [49]. Furthermore, some studies evaluated HIIT versus CAET for effects on blood pressure [43,47,[50][51][52], HR recovery and HR variability [51] as well as systolic function and systolic volumes [29,49] and found no effects of training on these variables. Finally, CAET seemed to confer better improvement in endothelial function as compared with HIIT [52].…”
Section: Hiit Versus Caet Programssupporting
confidence: 63%
“…Some were already included in the previous meta-analysis and represented part of the summarized effects, but some recent ones were not included [43][44][45]. From all reviewed studies, 4 showed a superior effect of HIIT over CAET on VȮ 2 peak and prescribed long intervals (4-min intervals at 80-95% HRpeak) [29,[45][46][47]. Similar benefits were found for HIIT versus CAET for VĖ=VĊO 2 slope, oxygen uptake efficiency slope [43], partial pressure of end-tidal CO 2 [48], coronary atheroma and plaque characteristics [44] and quality of life [49].…”
Section: Hiit Versus Caet Programsmentioning
confidence: 92%
See 1 more Smart Citation
“…They involved assessments of HIIT versus MCT for patients with CAD, including metabolic syndrome (n=10) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and CHF, including diastolic dysfunction (n=11) (15,16,(28)(29)(30)(31)(32)(33)(34)(35)(36). In the studies shown in Tables 1 and 2, although the VO2peak was not necessarily the primary endpoint, we presented the VO2peak at baseline and the percentage increase in the VO2peak during the exercise period in order to compare the two groups.…”
Section: Benefits Of Hiitmentioning
confidence: 99%
“…The study found that both groups improved aerobically but the HIIT group's improvement was 5% higher than the moderate intensity group. Steven et al (2014) [10] conducted a study of 39 patients to evaluate the effectiveness of HHIT in cardiac rehabilitation. This study recruited both genders with a broad age range of 18 -75 years, in a 3 day a week CR program.…”
Section: Literature Reviewmentioning
confidence: 99%